FAKTOR-FAKTOR YANG BERKONTRIBUSI TERHADAP KINERJA GURU DAN MUTU PEMBELAJARAN DI MADRASAH IBTIDAIYAH NEGERI KOTA BANDAR LAMPUNG - Siti Patimah, - (2007)
The implication of the lowness of quality of output graduated from Islamic Elementary School indicates the low quality of the learning and teaching process. Considering that teacher is one of the keys to get success in learning and teaching process, the effort to improve teacher's performance is a must. The efforts to improve learning quality and teacher's performance can be earned out in many ways. In this research, there are several factors which are supposed can contribute to learning quality and teacher's performance, namely self-development, stress, and work satisfaction.Self-development is the teacher's ability in responding the change to achieve the performance growth, development, and improvement or to get the work achievement. Work stress is the psychological experience which affects someone and the reaction toward the conditions. The stress appears as the result of pressure and strain come from someone who can not adjust to his/her work environment. And, work satisfaction is an emotional condition felt by teacher in the expression of pleasure and satisfaction of the situation in the work environment. The teacher's performance is a working process performed by teacher based on desire and ability in doing his/her duty clearly and relevantly. The result of teacher's performance is observable, both in quantity and quality. The learning quality proposed in this research is the learning process which contains effectiveness and efficiency of the whole factors or aspects playing a role in the learning process.This research was carried out by using quantitative approach and descriptive survey method. The population was all teachers of State Islamic Elementary School (MIN) Bandar Lampung. There were 132 teachers. By using Krecjie Morgan Formula, 56 teachers became the samples of this research. They were chosen by using Proportional Random Sampling. The data collection was done using questionnaires, and then they were analyzed by using descriptive statistic technique and path analysis.Data analysis showed the findings and conclusion as follow: firstly, there is a significant contribution of teachers' performances to learning quality in MIN Bandar Lampung that is 17 % with fair correlation (0.413); secondly, the significant contribution of self-development to the teachers' performances is 16.3% and to learning quality is 14 %. The correlation of self-development toward the teachers' performance is fair (0.403), and toward learning quality is also fair (0.374). Thirdly, there is a significant contribution of work stress toward teachers' performance that is 21.2% and to learning quality is 17.5%. The work stress has negative correlation toward teachers' performance that is (-0.460) and the negative correlation toward learning quality is fair (-0.419). Fourthly, the significant contribution of work satisfaction toward teachers' performance is 18.3% with fair correlation (0.428). The contribution of work satisfaction toward learning quality is 11% with low correlation (0.331). Fifthly, there is a significant contribution of self-development, work stress and work satisfaction simultaneously toward teachers' performance that is 38.3% with high correlation (0.619) and the contribution toward learning quality is 30.3% with fair correlation (0,550).Based on the finding, it can be assumed that the learning quality and the teacher's performance can be achieved through the efforts as follow: the improvement of self-development of the teachers by paying attention to them and facilitating the teacher's self-development to be improved optimally and maximally; the improvement of the work satisfaction by enhancing the prosperity of Islamic school teachers and giving them chances to develop and improve their carriers. Another important effort which should be our concern is that everything can stimulate teacher's stress should be prevented and eliminated.